Malignant pleural effusion treatment with Pleurx® catheter: first case in Costa Rica - Villalobos Garita, Karol (2015)
Malignant pleural effusion is a common complication of cancer, this entity represents a therapeutic challenge as the survival of patients with the disease is usually limited. We present the first reported case in Costa Rica of a PleurX® catheter insertion for symptomatic malignant pleural effusion management in a patient previously treated with multiple thoracenteses. This device is a new therapeutic alternative in Costa Rica for the treatment of this serious complication associated with a limited life prognosis and impaired quality of life.